KONSEP MEMBANGUN BRANDING IMAGE UNTUK MENINGKATKAN KEPERCAYAAN TERHADAP LEMBAGA PENDIDIKAN ISLAM - Carnawi, Carnawi; Hermawan, Iwan; Az Zahro, Fatimah (Program Studi Manajemen Pendidikan Islam, 2024)
This study delves into the concept of building a branding image to enhance public trust in Islamic educational institutions. In today’s competitive educational environment, it is vital for these institutions to not only provide high-quality education but also establish a strong, positive brand identity that resonates with their core values. Utilizing a qualitative research approach with phenomenological methods, the study uncovers that effective branding strategies go beyond mere promotion; they involve management practices that demonstrate integrity, transparency, and a steadfast commitment to educational excellence. The research findings indicate that Islamic educational institutions that successfully manage their branding can significantly enhance public trust, bolster their competitive position globally, and contribute to shaping a generation grounded in moral integrity and academic excellence. By understanding and implementing these branding strategies, these institutions can effectively communicate their values, meet community needs, and ensure their continued relevance and success in an increasingly competitive global educational landscape.